Mississippi Black History Makers - Sewell, George Alexander (Book collections on Project MUSE., 1984)
This new edition of biographical sketches of notable blacks from Mississippi expands the edition published in 1977. A total of 166 figures are included in this new printing, all of them persons who have, by the authors' comprehensive survey, ""made significant contributions in bringing about the uplift of the black race.""Black history makers are defined herein as those who have achieved national prominence in their fields, have made lasting contributions within the state as pioneers in fields where blacks were not previously allowed, or contributed in their own community or field, representin.